Analysis of the Needs for Developing Digital Learning Media to Improve Concept Mastery and Collaboration - Candra Dwinata; Wulandari Saputri; Meli Astriani (Jurnal Pijar MIPA, 2026)
Education is currently one of the most important aspects of human life. Education is the process of developing students' abilities. The importance of developing learning media is that using them can help students understand complex, abstract material more simply. This study aims to analyze the need for learning media in biology material at MA Darussalam Lempuing OKI. This study employed quantitative descriptive analysis techniques. Data collection used a questionnaire, with subjects being 11th-grade students and biology teachers at MA Darussalam Lempuing, OKI. The sample for this study consisted of 30 students. The analysis showed that only 23% of activities supported student collaboration, and that 60% of students' conceptual understanding remained low. This was influenced by the use of less engaging learning media, such as PPT (50%), YouTube (33%), and visual aids (17%). Furthermore, the teaching method used by teachers remained dominated by lectures (57%), leading to student boredom and disinterest. Thus, a flashcard learning media integrated with augmented reality is needed to improve students' collaboration skills and their mastery of concepts through the TGT model.